Issues in Islamic law - Ansari, Abdul Haseeb (Serials Publications, 2010)
From the Islamic point of view also, jurisprudence can be said to be a scientific study of legal of legal precepts in the light of techniques and relevant rules of others related contained in the Qur’an and the Sunnah. Principles of law are in the from of commands having divine wisdom have been made known to the man through the Qur’an and the Sunnah of the Prophet (saw) (prophetic traditions: what Prophet did, decided on disputes and asked people to do or abstain from doing). The Sunnah comprise principle derived from ahadith (plural of hadith, narrations by Prophet’s companions about what Prophet did in his life, decided on doing). They together constitute the basic source of legal principles. Since they provide only basic principles, detailed rules to meet the challenges erupting in the society are required to be made by followers of Islam themselves. Islam, thus, encourages its followers to further means by application of laws hased on human wisdom, has to be determined on the basis of the basics sources, the Qur’an and the Sunnah. Any man-made law if does not conform to them, stands invalid and thus not to be followed, unless there are compelling circumstances. Even in these circumstances any man-made law has to be followed in a limited form, with a predominant sense of reluctance. For example, Muslim jurists are of the opinion that haram (prohibited) things become halal (allowable) in a compelling circumstance, like a medicine has alcohol, which is necessary to be taken, and any non-alcoholic alternative is not available. A Muslim can take that medicine only in a limited quantity, as determined by the doctor with a predominant sense of reluctance. Broadly speaking, mouthwash and cough syrup having alcohol are not permissible because both have both have alcoholic alternatives.